2010
DOI: 10.1242/jeb.037135
|View full text |Cite
|
Sign up to set email alerts
|

Target tracking during venom ‘spitting’ by cobras

Abstract: SUMMARY Spitting cobras, which defend themselves by streaming venom towards the face and/or eyes of a predator, must be highly accurate because the venom they spit is only an effective deterrent if it lands on the predator's cornea. Several factors make this level of accuracy difficult to achieve; the target is moving, is frequently >1 m away from the snake and the venom stream is released in approximately 50 ms. In the present study we show that spitting cobras can accurately track the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Spitting patterns on the photos showed that the venom streamlines are either between the eyes or at one eye, suggesting the intent to hit at least one eye of an aggressor. Another group investigated target tracking during cobra venom spitting [ 8 ]. They observed that cobras perform rapid cephalic oscillations to coordinate the target’s movements, for increasing the chance of hitting the eyes.…”
Section: Snake Venom/toxin Cause Ocular Complicationsmentioning
confidence: 99%
“…Spitting patterns on the photos showed that the venom streamlines are either between the eyes or at one eye, suggesting the intent to hit at least one eye of an aggressor. Another group investigated target tracking during cobra venom spitting [ 8 ]. They observed that cobras perform rapid cephalic oscillations to coordinate the target’s movements, for increasing the chance of hitting the eyes.…”
Section: Snake Venom/toxin Cause Ocular Complicationsmentioning
confidence: 99%
“…Targeting, as measured using head movements, therefore provides a useful overall measure of a participant's ability to follow a fast moving prey item, while providing a measure of biological realism in the context of predator-prey interactions (where animals often align their head with the target before attack; e.g. [27,28]).…”
Section: Methods (A) Simulationsmentioning
confidence: 99%
“…Asian spitting cobras (Naja: subgenus Naja) and the rinkhals (monotypic Hemachatus). All use modified fangs with small, rounded, front-facing orifices (7) to produce a spray of venom, which may reach distances of 2.5 m (8), and targets the eyes of an aggressor (9) (Fig. S1).…”
Section: Main Textmentioning
confidence: 99%